2016
DOI: 10.4018/ijkdb.2016070104
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Toxicity of Conventional Triazole Pesticides by Simulating Inhibitory Effect on Human Aromatase CYP19 Enzyme

Abstract: 15 common fungicides were evaluated to study their inhibitory effects on the human aromatase enzyme in comparison with the Letrozole (LTZ), the most potent inhibitor of aromatase (AI) used as anti-estrogen for breast cancer treatment using AUTODOCK software for calculation of inhibition energy on CYP19A1 aromatase enzyme. Those compounds with minimal binding energy are safer in terms of toxicity and resistance of other prescription drugs like non-steroid AIs. In the authors' study, they found that four triazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Fard et al (2016) found a negative effect of risatriptan on hepatocytes. Hepatocyte lysosomes and mitochondria have been shown to play an important role in risatriptan-induced cell injury (Chachibaia & Hoskeri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fard et al (2016) found a negative effect of risatriptan on hepatocytes. Hepatocyte lysosomes and mitochondria have been shown to play an important role in risatriptan-induced cell injury (Chachibaia & Hoskeri, 2016).…”
Section: Introductionmentioning
confidence: 99%